1997
DOI: 10.1242/dev.124.12.2451
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of programmed cell death in morphogenesis of the vertebrate inner ear

Abstract: An outstanding challenge in developmental biology is to reveal the mechanisms underlying the morphogenesis of complex organs. A striking example is the developing inner ear of the vertebrate, which acquires a precise three-dimensional arrangement of its constituent epithelial cells to form three semicircular canals, a central vestibule and a coiled cochlea (in mammals). In generating a semicircular canal, epithelial cells seem to ‘disappear’ from the center of each canal. This phenomenon has been variously exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Previous studies demonstrated that the presence of certain immune cells present in the mature inner ear is linked to the hair cell damage in both the cochlea and vestibular organs of mammals 44 46 . The up-regulation of certain immunoregulatory pathways starting from E12.5 may be related to the immune cell proliferation or apoptosis in the developmental process, which has been documented beginning from the otic cup stage to birth 47 49 . Since immune-mediated inner ear disease and sensorineural hearing loss have been widely recognized 50 , 51 , further studies of TFs related to immunoregulation may shed light on the future immunotherapy for the inner ear diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the presence of certain immune cells present in the mature inner ear is linked to the hair cell damage in both the cochlea and vestibular organs of mammals 44 46 . The up-regulation of certain immunoregulatory pathways starting from E12.5 may be related to the immune cell proliferation or apoptosis in the developmental process, which has been documented beginning from the otic cup stage to birth 47 49 . Since immune-mediated inner ear disease and sensorineural hearing loss have been widely recognized 50 , 51 , further studies of TFs related to immunoregulation may shed light on the future immunotherapy for the inner ear diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our study supports the key regulatory studies demonstrated that the presence of certain immune cells present in the mature inner ear is linked to the hair cell damage in both the cochlea and vestibular organs of mammals (39)(40)(41). The up-regulation of certain immunoregulatory pathways starting from E12.5 may be related to the immune cell proliferation or apoptosis in the developmental process, which has been documented beginning from the otic cup stage to birth (42)(43)(44). Since immune-mediated inner ear disease and sensorineural hearing loss have been widely recognized (45,46), further studies of TFs related to immunoregulation may shed light on the future immunotherapy for the inner ear diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this reduction in region-specific apoptosis, embryos of the mouse mutants exhibited neurulation defects in the hindbrain. The necessity of cell apoptosis in morphogenesis has also been reported in several tissues, e.g., the inner ear (Fekete et al 1997), optic-cup (Trousse et al 2001), brain, (Kuan et al 2000), limb bud (Suzanne and Steller 2013), and heart (Zhao and Rivkees 2000). In morphogenesis, the timing and region of cell apoptosis are specific.…”
Section: Introductionmentioning
confidence: 88%
“…To establish that successive cell apoptosis and rearrangements could be expressed by the proposed model, we performed further simulations of morphogenesis driven by region-specific cell apoptosis. Because region-specific cell apoptosis is often observed in embryogenesis (Fekete et al 1997;Trousse et al 2001;Kuan et al 2000;Suzanne and Steller 2013;Zhao and Rivkees 2000), it has biological as well as numerical importance to apply the proposed model to the morphogenesis driven by regionspecific cell apoptosis. The employed initial condition is as follows.…”
Section: Cell Rearrangements Driven By Region-specific Cell Apoptosismentioning
confidence: 99%